Thread: Factoring x^3 + 6x = 6x^2 + 8?

1. Factoring x^3 + 6x = 6x^2 + 8?

Factoring x^3 + 6x = 6x^2 + 8?

hello. i can't seem to figure out how to factor this equation without a calculator . help would be greatly appreciated

x^3 + 6x = 6x^2 + 8

2. that's because it's not factorable ... you'll need to use technology or
The "Cubic Formula" to solve it.

3. Originally Posted by guitarplaya08
Factoring x^3 + 6x = 6x^2 + 8?

hello. i can't seem to figure out how to factor this equation without a calculator . help would be greatly appreciated

x^3 + 6x = 6x^2 - 8
Bring all the terms on one side,

$\displaystyle x^3-6x^2+6x+8=0$

If we substitute x=4 in this equation, its value =0.

so, (x-4) is one factor. Now divide the expression by (x-4)

we got $\displaystyle x^2-2x-2$

So, the expression is $\displaystyle (x-4)(x^2-2x-2)=0$

4. Originally Posted by guitarplaya08
Factoring x^3 + 6x = 6x^2 + 8?

hello. i can't seem to figure out how to factor this equation without a calculator . help would be greatly appreciated

x^3 + 6x = 6x^2 + 8
Originally Posted by skeeter
that's because it's not factorable ... you'll need to use technology or
The "Cubic Formula" to solve it.
Originally Posted by Shyam
Originally Posted by guitarplaya08
Factoring x^3 + 6x = 6x^2 + 8?

hello. i can't seem to figure out how to factor this equation without a calculator . help would be greatly appreciated

x^3 + 6x = 6x^2 - 8
Bring all the terms on one side,

$\displaystyle x^3-6x^2+6x+8=0$

If we substitute x=4 in this equation, its value =0.

so, (x-4) is one factor. Now divide the expression by (x-4)

we got $\displaystyle x^2-2x-2$

So, the expression is $\displaystyle (x-4)(x^2-2x-2)=0$
It looks like something screwy is going on .......

Word to the wise, skeeter ...... Quote the OP when replying .....